Synthesis and Characterization of PMMA/ZnS Micro-Nanocomposite Spheres - Chen, Bi-Yun; Liu, Jin; Li, Zhen; Lu, Bing-Bing; Zeng, Shao-Hua (Asian Journal of Chemistry, 2014)
In this study, PMMA/ZnS micro-nanocomposite spheres were successfully synthesized by precipitation method using self-made poly methyl methacrylate (PMMA) particles as the core template. The effects of different reaction conditions on the morphology and structure of the synthesized particles were studied and characterized by scanning electron microscope, X-ray diffraction and energy dispersive spectrometer. The results indicated that PMMA/ZnS micro-nanocomposite spheres were optimally prepared by pretreating at 50 ºC for 6 h. The morphology and the amount of ZnS on the surface of the as-prepared spheres could be controlled by prolonging pretreatment time, reaction temperature, changing material ratio, etc.